2017
DOI: 10.1111/brv.12329
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of variation in offspring body mass: meta‐analyses in birds and mammals

Abstract: Early survival is highly variable and strongly influences observed population growth rates in most vertebrate populations. One of the major potential drivers of survival variation among juveniles is body mass. Heavy juveniles are better fed and have greater body reserves, and are thus assumed to survive better than light individuals. In spite of this, some studies have failed to detect an influence of body mass on offspring survival, questioning whether offspring body mass does indeed consistently influence ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 272 publications
(128 reference statements)
10
82
1
Order By: Relevance
“…A recent meta-analysis showed that maternal mass provides a reliable predictor of offspring birth mass in mammals (Ronget et al, 2018). However, heavier females in autumn had a higher probability of lactation the following year (GLMM, b = 1.25, 95% CI [0.84, 1.71]) and their lambs were more likely to survive the neonatal period (GLMM, b = 0.32, 95% CI [0.15, 0.48]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis showed that maternal mass provides a reliable predictor of offspring birth mass in mammals (Ronget et al, 2018). However, heavier females in autumn had a higher probability of lactation the following year (GLMM, b = 1.25, 95% CI [0.84, 1.71]) and their lambs were more likely to survive the neonatal period (GLMM, b = 0.32, 95% CI [0.15, 0.48]).…”
Section: Discussionmentioning
confidence: 99%
“…Lamb mortality is approximately three times greater in winter than in summer (Portier et al 1998). Because heavy female mammals generally produce heavy offspring that show high survival rates (Ronget et al, 2018;see Clutton-Brock et al 1996, Griffin et al 2011 for case studies), we expected that lamb survival should increase with mid-September maternal mass. Because females that lost more mass during winter must gain more mass during the following summer (Pelletier et al 2007b), and because mothers favor their own summer mass gain over the growth of their lambs (Festa-Bianchet and Jorgenson 1998), we predicted that lamb summer mass gain should be lower for mothers that lost relatively more mass during the previous winter.…”
Section: Introductionmentioning
confidence: 96%
“…In France, the impact of warming on avian population dynamics may impact body size negatively at the warmest sites, corresponding to the Mediterranean region, where species (including our study species) live closer to the upper boundary of their thermal tolerance (Jiguet et al, ). As individual fitness is often size‐dependent, with the largest surviving and/or reproducing better (Lindström, ; Ronget et al, ), it is to be feared that size decline may impact populations negatively. To assess the robustness and generality of our conclusions, future studies should investigate the synergistic effects of local temperature anomalies (weather fluctuations) and local average temperatures (climate) on body size across a larger number of species (including a broader spectrum of life‐history traits, and particularly more thermal specialists), and across a broader climatic range, to include the entire thermal ranges of the species studied.…”
Section: Discussionmentioning
confidence: 99%
“…Festa-Bianchet, Gaillard, & Jorgenson, 1998;Ronget et al, 2018;Schick et al, 2013;Sheldon & West, 2004). Festa-Bianchet, Gaillard, & Jorgenson, 1998;Ronget et al, 2018;Schick et al, 2013;Sheldon & West, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Resource limitation forces long-lived iteroparous animals to trade off survival, growth, and reproduction during their lifetime (e.g. Festa-Bianchet, Gaillard, & Jorgenson, 1998;Ronget et al, 2018;Schick et al, 2013;Sheldon & West, 2004). Body composition provides a measure of the immediate phenotypic quality of individuals within a population and can serve as a rough proxy for their relative fitness-animals in 'good' condition can fulfil their own energetic needs and store spare resources for future use, potentially deriving fitness benefits over the long term (Speakman, 2001).…”
Section: Introductionmentioning
confidence: 99%